Application of constant amplitude dynamic tests for life prediction of air springs at various control parameters - Bešter, Tomaž (Strojniški vestnik, 2014)
Air spring manufactures use constant amplitude tests for the quality validation of air springs. The tests are very simple and the only information we get from them is that a spring is adequate if it passes the test and inadequate if it does not. One of the objectives of this article is to use these tests to make life predictions based on the standardised load spectrum. This prediction is made with force as the damage parameter. The second objective is to determine if it is possible to use experimental results obtained at one control parameter, e.g. force, to make life predictions for another control parameter, e.g. stress. With equations it is proved that such transformation is possible.
Keywords: časovna trdnost; dinamični preizkusi; obremenitveni kolektiv; podvozje vozila; utrujanje; zračne vzmeti